2016
DOI: 10.1021/acsami.6b03371
|View full text |Cite
|
Sign up to set email alerts
|

Cofacial Versus Coplanar Arrangement in Centrosymmetric Packing Dimers of Dipolar Small Molecules: Structural Effects on the Crystallization Behaviors and Optoelectronic Characteristics

Abstract: Two D-π-A-A molecules (MIDTP and TIDTP) composed of an electron-rich ditolylamino group (D) and an electron-deficient 5-dicyanovinylenylpyrimidine (A-A) fragment bridged together with indeno[1,2-b]thiophene (IDT) were synthesized. These molecules provide an opportunity to examine in-depth the impact of side-chain variations (methyl vs p-tolyl) on the crystallization behaviors, solid-state morphology, physical properties, and optoelectronic characteristics relevant for practical applications. X-ray analyses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A low HOMO-LUMO gap, and by extension a low optical gap, ensures the generated oligomers are promising materials for organic photovoltaics, and a low dipole moment in the ground state is desired as it has been shown that this can help with directing self-assembly towards supramolecular arrangements that promote macroscopic properties such as charge-carrier mobility. 33 Our approach would be equally applicable to a focus on a different region of property space and we would note that for optoelectronic device applications such as OPVs and OLEDs, it is typical for there to be multiple material properties and device characteristics contributing to high performance, and these would need to be considered and appropriately weighted on a case-by-case basis. We discuss the challenges for further extension of the method in the discussion.…”
Section: Introductionmentioning
confidence: 99%
“…A low HOMO-LUMO gap, and by extension a low optical gap, ensures the generated oligomers are promising materials for organic photovoltaics, and a low dipole moment in the ground state is desired as it has been shown that this can help with directing self-assembly towards supramolecular arrangements that promote macroscopic properties such as charge-carrier mobility. 33 Our approach would be equally applicable to a focus on a different region of property space and we would note that for optoelectronic device applications such as OPVs and OLEDs, it is typical for there to be multiple material properties and device characteristics contributing to high performance, and these would need to be considered and appropriately weighted on a case-by-case basis. We discuss the challenges for further extension of the method in the discussion.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last 25 years, there has been a considerable interest in the design of organic push‐pull chromophores having electron‐donating group (D) linked to an electron‐withdrawing one (A) via a π‐conjugated bridge (D–π‐A structure) In these compounds, intramolecular charge transfer (ICT) occurs and generation of new low‐energy molecular orbital induces unique optical and electrochemical properties . These chromophores have found key applications as fluorescent sensors, in optoelectronic, particularly for photovoltaics, organic field‐effect transistors (OFETs) and in organic light‐emitting diodes (OLEDs) . The generation of a molecular dipole in push‐pull chromophores induces also nonlinear optical (NLO) properties such as second order NLO phenomena and two‐photon absorption (TPA).…”
Section: Introductionmentioning
confidence: 99%
“…A low HOMO-LUMO gap ensures the generated oligomers are promising materials for organic photovoltaics, and a low dipole moment in the ground state is desired as it has been shown that this can help with directing selfassembly towards supramolecular arrangements that promote macroscopic properties such as charge-carrier mobility. 30 Our approach would be equally applicable to a focus on a different region of property space.…”
Section: Introductionmentioning
confidence: 99%